2018
DOI: 10.1108/ijse-10-2016-0291
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of enrolment in the NHIS for women in Ghana – a cross sectional study

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent Abstract BackgroundThe National Health Insurance Scheme (NHIS) was introduced in 2005 to provide equitable access to healthcare. Furthermore, concessions were made for pregnant women, yet inequities in access continue to exist. This study explores whether dimensions of social exclusion explain why some groups of women are not benefitting from the scheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 33 publications
5
9
1
Order By: Relevance
“…The finding is consistent with other studies that showed that higher SES is an important predictor of enrolment in NHIS. 3,22,23,26,31,33,34,37,38,41,42 Being a formal worker was a significant predictor of enrolment in NHIS among women of reproductive age in this study. A plausible explanation for this observation is that formal workers earn income that is easily deducted as part of contribution towards the purchase of health insurance.…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations
“…The finding is consistent with other studies that showed that higher SES is an important predictor of enrolment in NHIS. 3,22,23,26,31,33,34,37,38,41,42 Being a formal worker was a significant predictor of enrolment in NHIS among women of reproductive age in this study. A plausible explanation for this observation is that formal workers earn income that is easily deducted as part of contribution towards the purchase of health insurance.…”
Section: Discussionsupporting
confidence: 45%
“…However, this finding is in contrast to results from other studies. 22,26,27,34,35,38 In this study, women in North West region, South East region, South South region and South West region were less likely to have health insurance. The low level of enrolment in these geographical locations could be due to the fact that they are predominantly rural and have a high proportion of women from poor households who do not have knowledge of the advantages of health insurance.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The results of the multivariate analysis found that wealth status is one of the determinants of health insurance ownership among pregnant women. This nding con rms the results of previous studies with the same research theme in Nigeria and Ghana which informed that those who have good wealth status are more likely to participate in health insurance 22,28,29 . Pregnant women with low wealth status probably do not have a xed source of income.…”
Section: Discussionsupporting
confidence: 87%